Case Report: Bilateral Renal Cell Carcinoma With Different Histological and Morphological Features, Clear Cell and Cystic Thyroid-Like Follicular Subtype - Ni, Jinsong; Cui, Ni; Wang, Yanfang; Liu, Jixuan (Frontiers in Oncology, 2021)
Thyroid-like follicular renal cell carcinoma is a rare subtype of renal cell carcinoma that has only been recently recognized, as most cases involve a solid tumor in one kidney. In this study, we report a rare case of bilateral renal cell carcinoma wherein the tumor in the left kidney was diagnosed as clear cell carcinoma, while the tumor in right kidney as thyroid-like follicular renal cell carcinoma. The difference between this case and the ones described in previous reports is that thyroid-like follicular renal cell carcinoma showed cystic changes on imaging. This suggests that when renal cystic lesions are encountered, we should consider the possibility of such rare tumors.